Are recurrence of ischemic mitral regurgitation and left ventricular reverse remodeling after restrictive annuloplasty ring dependent?. (15th June 2020) - Micali, Linda Renata; Parise, Gianmarco; Moula, Amalia Ioanna; Alayed, Yazeed; Parise, Orlando; Matteucci, Francesco; de Jong, Monique; Tetta, Cecilia; Gelsomino, Sandro
Abstract: Objective: This meta-analysis investigates MR recurrence and degree of left ventricular reverse remodeling (LVRR) in CIMR patients in mitral annuloplasty employing different ring designs. Background: The deeper understanding of complex changes caused by chronic ischemic mitral regurgitation (CIMR) have led to new generations of rings that, by maintaining normal 3D annular geometry are supposed to enhance long-term repair durability. Methods: A meta-analysis of all available reports in literature of MV repair through different ring design was conducted. Meta-regression was performed to investigate the impact of mitral ring characteristics related to flexibility, planarity, symmetry and single type utilized. Twenty studies encompassing a total of 1876 patients were included at the end of the selection process. Results: At meta-regression recurrence of MR was not influenced by the ring employed. Nonetheless, the event rate of MR recurrence in planar rings was 19%. Vs. 11% observed with non-planar rings. Recurrence rate in patients implanted with symmetric rings was 14% whereas it was 7% in asymmetric rings. The non-planar asymmetric IMR-ETlogix showed the lowest recurrence rate (6%). Furthermore, in planar group the reduction of pre- and post-operative LVEDD was - 4%. In the non-planar group, the LVEDD was reduced by 8.6%. In patients implanted with symmetric rings LVEDD reduction was 10.8%. LVRR in the asymmetric group was −5.8%. Conclusion: MR recurrence occurred the least with asymmetric rings with less disproportionate asymmetry. In contrast, LVRR occurred at a greater extent in symmetric rings. Highlights: MR Recurrence was not influenced by the ring employed. IMR-ETlogix showed the lowest MR recurrence rate. LV Reverse remodeling was comparable in planar and non-planar rings. Symmetric rings showed higher LV remodeling.